PERKEMBANGAN FISIK KOTA KUALA KURUN KECAMATAN KURUN KABUPATEN GUNUNG MAS - , HERMAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
City of Kuala kurun is a new city that was initially existed as a village, and at once the Capital District Kurun, Kapuas Regency. Access is limited, the scope of a large area, and the limited development budget in Kapuas Regency Government, making the lack of program development in each area. Neither the Kuala, which even at that time its status as the Capital District, as well as a work area of the Office of the Vice Regent of Kapuas, Gunung Mas area. Development of Kuala Kurun starting to look up since the entry Transabangdep program in 1992, and has increased significantly since the enactment as Gunung Mas Capital Regency since 2002. The research objective was to describe the physical development of the City of Kuala Kurun prior to 1992 to 2012, which is divided into three (3) periods of urban development and also to determine the factors that influence its development. The study was conducted with qualitative deductive method with a rationalistic-historical approach. Study site is part of the town center which is the Effective Urban Areas located in the two village of Kuala Kurun dan Tampang Tumbang Anjir. The analysis technique used is the exploration of any kind of data source interviews, observations and secondary data, so it can be sorted according to time period. These data were mapped to obtain the shape and direction of the change trend of physical development of the city and find out the factors that influence it in each period. The results showed that there has been a change in the pattern and structure of city hall in the city of Kuala Kurun since entering Transabangdep Program in 1992. Neighborhood activity center that was originally only being on the edge Kahayan River, since Regency Redistricting slowly shifting to the west of City Center which leads to the location Transabangdep as development centers. Based on its development from 1992 to 2012, the direction of propagation of Kuala Kurun occurs concentrically solidified (Concentric development) in the old city and the new settlement at the site Transabangdep, Linear elongated (linear development) on the road to Transabangdep and Tewah District, and jump (leap frog development) in some areas there are Government facilities. Thus Kuala Kurun undergo developmental changes in direction during the period 1992 - 2012, particularly in the period 2002-2012. Development of Kuala Kurun influenced by these factors: (1) Government Policy, (2) Accessibility (the Kahayan River existence and Road Networks), (3) Facilities Office, (4) Population, Social and Economic (5) Topography. From these factors is the most dominant factor of the Government policy.